A great place to have a war : America in Laos and the birth of a military CIA - Kurlantzick, Joshua (Simon & Schuster, 2017)
1960. President Eisenhower was focused on Laos, a tiny Southeast Asian nation. Washington feared the country would fall to communism, triggering a domino effect in the rest of Southeast Asia. In January 1961, Eisenhower approved the CIA's Operation Momentum, a plan to create a proxy army of ethnic Hmong to fight communist forces in Laos. Kurlantzick shows how the brutal war lasted nearly two decades, killed